A Case Report and Literature Review of Clostridium difficile Negative Antibiotic Associated Hemorrhagic Colitis Caused by Klebsiella oxytoca - Aaron Fisher; Alexandra Halalau (Case Reports in Gastrointestinal Medicine)
Klebsiella oxytoca hemorrhagic colitis is a rare form of antibiotic associated hemorrhagic colitis that is Clostridium difficile negative. Klebsiella oxytoca colitis has been shown to be triggered by penicillin administration, yet other antibiotics have been implicated as well. It can mimic the appearance of ischemic colitis on endoscopy; however it will generally be found in young, otherwise healthy patients without risk factors. We present a case of a 33-year-old Caucasian female who presented to the emergency room with profuse, bloody diarrhea for 5 days, after a one-week course of ampicillin. Colonoscopy was notable for ulcerated mucosa with erythema and easy friability and the biopsy was suggestive of ischemic colitis. Stool culture was positive for many Klebsiella oxytoca. The patient was discharged home with resolution of symptoms after three days in the hospital. She was instructed to avoid penicillin antibiotics and minimize nonsteroidal anti-inflammatory drug use.